Biblical Redaction and the Emergence of Absolute Monotheism: Implications for Religious Dialogue and Socio-Political Stability - Omosor, Festus Osom (NIU Journal of Humanities, 2020)
One of the most fundamental causes of religious intolerance is the proclamation of absolute or exclusive monotheism. Across the globe, religious intolerance with the attendant violence is principally associated with the Abrahamic religions, namely, Judaism, Christianity and Islam. Of all three, Judaism is not just the oldest but the mother of the rest two. The Hebrew Bible, which is the text of Judaism, appears to paint the picture of a nation that knew and worshipped only one God from the inception of their existence as a nation. But a critical study of the Hebrew Text reveals evidences to the contrary, namely, that the monotheism of the people of Israel was an evolutionary phenomenon that culminated in the post exilic era with biblical redactors playing key roles in shaping the absolute monotheistic theology of the Old Testament. This redactional influence on the Hebrew Bible and the implications for religious dialogue and socio-political stability has often been undermined in scholarly discussions. This is the engagement if this paper. The study employs the exegetical and hermeneutical methods applied within the framework of the redaction theory. Selected texts are exegetically studied to show the evidence of monotheistic redaction in the Old Testament. The paper concludes that the absolute monotheism of the Bible was a creation of theological editors and it has negative implications for religious relations and social stability. It recommends that to attain positive religious dialogue, monotheism must be liberal, relative, inclusive and therefore, tolerant. Keywords: Redaction, monotheism, intolerance, dialogue, socio-political, stability.